The Effect of Audiovisual Media Based Education on Changes in Adolescent's Attitudes Related to Cigarette Advertising (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2021)
Smoking behavior among adolescents is increasing. This condition is partly influenced by the incessant advertisements for cigarettes that offer expectations that are the opposite of their impact. This study aims to determine the effect of audiovisual media-based education in the context of changing adolescent attitudes towards cigarette advertisements. The study design used was a Quasi Experiment with a Pretest-Posttest with Control Group. The research subjects were college adolescents (students) with a total of 25 people in the intervention group and 25 in the control group. Data were analyzed using dependent t test and independent t test. In the intervention group, there was a significant difference between attitudes towards cigarette advertisements before and after being given audiovisual media related to cigarette advertising in the experimental group (p = 0.010), on the other hand there was no change in attitude in the control group (p = 0.760) . However, there was no significant difference between attitudes towards cigarette advertising in the experimental and control groups (p = 0.096). Therefore, education using audiovisual media is considered more effective in increasing changes in attitudes towards cigarette advertisements. The campus is expected to reinforce and socialize regulations related to KTR and further research can conduct media pre-testing.